52 Effects of an energy or protein supplement on forage dry matter intake for steers grazing summer native range. (28th November 2020) - Husz, Taylor C; Beck, Paul A; Foote, Andrew P; Reuter, Ryan R
Abstract: The objective of this study was to determine the effects of supplementation level and type on forage intake of steers grazing a high-quality native range. This study was conducted in late May through the end of June. On d 0, steers (n=16, initial BW = 193.7 kg ± 14.3 kg) were randomly assigned to one of 5 dietary treatments, fed once daily in individual stalls for 28 d. Treatments were control (no supplement, n=4), or supplemented with either cottonseed meal or dry rolled corn, each at either 0.45 kg or 1.81 kg as-fed/d (n=3 for each combination). Beginning on d 7, steers were orally administered titanium dioxide boluses (10 g/steer) once daily for 21 d. Fecal samples were collected from the rectum once daily for 14 d, analyzed for Ti concentration via a handheld X-ray fluorescence analyzer, and total fecal output was estimated. Diet digestibility was estimated after a 288-h in situ incubation of forage and fecal samples to determine indigestible NDF. Some steers had orts, therefore actual mean supplement intake was used in analysis. Results were analyzed with regression, with animal as the experimental unit. Mean estimated forage DMI of unsupplemented animals was 1.6% BW. Contrary to expectation, corn supplemented steers exhibited greater forage DMI as a percentage of BW than cottonseed meal supplemented steers (P = 0.01; 1.5 vs. 1.1, respectively).